Philosophy and Exegesis in al-Fârâbî, Averroes, and Maimonides - Fraenkel, Carlos (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2008)
AbstractMaimonides and Averroes shared in many respects a philosophical-religious outlook and have been described as disciples of al-Fârâbî, the founder of the school of Arabic Aristotelianism (falsafa). At first view, however, their legacy could hardly be more different : while Averroes wrote almost only commentaries on Aristotle, Maimonides did not write a single work that, strictly speaking, falls into a traditional philosophical genre. He is, on the other hand, a prominent commentator as well — only that instead of explicating Aristotle, he comments on the Law of Moses. The main question I address in this paper is whether this strikingly different relation to philosophy and exegesis in Averroes and Maimonides can be explained as two ways of implementing a conceptual framework established by al-Fârâbî. I first examine al-Fârâbî’s project, which I suggest is determined by a twofold task : to take up and continue the project of ancient philosophy and to define its place in a society in which the authority of the divine Law is undisputed. Then I argue that while Averroes’ work can on the whole be understood as continuing al-Fârâbî’s project, this is only in a qualified way true for Maimonides who in part creatively transforms al-Fârâbî and in part relies on premises that can clearly not be derived from al-Fârâbî. Maimonides’ position on philosophy and exegesis is in important respects different from the standard position of the falâsifa — and this had far-reaching implications for later medieval Jewish philosophy.